Insulin-Like Peptide 3 (INSL3) Serum Concentration During Human Male Fetal Life - Harrison, Steven M.; Bush, Nicol Corbin; Wang, Yi; Mucher, Zachary R.; Lorenzo, Armando J.; Grimsby, Gwen M.; Schlomer, Bruce J.; Büllesbach, Erika E.; Baker, Linda A. (Frontiers in Endocrinology, 2019)
Context: Insulin-like peptide 3 (INSL3), a protein hormone produced by Leydig cells, may play a crucial role in testicular descent as male INSL3 knockout mice have bilateral cryptorchidism. Previous studies have measured human fetal INSL3 levels in amniotic fluid only. Objective: To measure INSL3 serum levels and mRNA in fetal umbilical cord blood and fetal testes, respectively. Design: INSL3 concentrations were assayed on 50μl of serum from male human fetal umbilical cord blood by a non-commercial highly sensitive and specific radioimmunoassay. For secondary confirmation, quantitative real-time PCR was used to measure INSL3 relative mRNA expression in 7 age-matched human fetal testes. Setting: UT Southwestern Medical Center, Dallas, TX and Medical University of South Carolina, Charleston, SC. Patients or other Participants: Twelve human male umbilical cord blood samples and 7 human male testes were obtained from fetuses 14-21 weeks gestation. Male sex was verified by leukocyte genomic DNA SRY PCR. Interventions: None. Main Outcome Measures: Human male fetal INSL3 cord blood serum concentrations and testicular relative mRNA expression. Results: INSL3 serum concentrations during human male gestational weeks 15–20 were 2-4 times higher than published prepubertal male levels and were 5-100 times higher than previous reports of INSL3 concentrations obtained from amniotic fluid. Testicular fetal INSL3 mRNA relative expression was low from weeks 14-16, rose significantly weeks 17 and 18, and returned to low levels at week 21. Conclusions: These findings further support the role of INSL3 in human testicular descent and could prove relevant in uncovering the pathophysiology of cryptorchidism.